Motivasi Belajar dalam Mengikuti Pembelajaran Daring Siswa Kelas X SMA - Wardhana, Damara Putri; Hidayat, Rian Rokhmad; Purwaningrum, Ribut (Universitas Sebelas Maret, 2023)
This study aims to analyze the level of learning motivation of class X, differences in learning motivation between male and female and differences in motivation learning between students majoring in science and social studies, difference in scores between before online learning and after online learning at SMAN 2 Surakarta. This study uses a quantitative research approach with survey research methods. The sample in this study was 190 students of class X at SMAN 2 Surakarta with non- probability sampling technique. Data collection techniques using a questionnaire. The data analysis in this study used descriptive analysis, independent sample t-test and paired sample t-test. The results of this study indicate that (1) the students of class X at SMAN 2 Surakarta have moderate learning motivation, (2) there is no significant difference between the learning motivation of male students and female students, (3) no significant difference was found between the learning motivation of students majoring in science and students majoring in social studies, (4) no significant difference was found between student learning outcomes before online learning and after online learning.